Звільнення з п. 7 ст. 40 КЗПП України: теорія і практика застосування - Бущенко, П. А.; Ветухова, І. А. (Право, 2016)
The article discusses theoretical and practical issues concerning the grounds and procedure for dismissal of paragraph 7 of article 40 of the Labor code of Ukraine for the appearing intoxicated, under the influence of drugs or other toxic substances employee at work. The historical aspect of the development of labor legislation and judicial practice in relation to regulation of the specified grounds of dismissal are considered. For upgrading labor legislation under the termination of the employment contract, conclusions were drawn and suggestions were given. // У статті розглядаються теоретичні та практичні питання, пов'язані з підставою та порядок звільнення пункту 7 статті 40 Трудового кодексу України для виявлення сп'яніння, під впливом ліків або інших токсичних речовин працівникам на роботі. Розглянуто історичний аспект розвитку трудового законодавства та судової практики щодо регулювання зазначених підстав звільнення. Для модернізації трудового законодавства при припиненні трудового договору було зроблено висновки та надані пропозиції.
The dismissal according to the p. 7 art. 40 of the labor code of Ukraine: theory and practice of application
Keywords: emergence at work in a state of intoxication; working time; suspension from work; dismissal; виникнення на роботі в стані інтоксикації; робочий час; призупинення від роботи; звільнення